2019
DOI: 10.26911/thejmch.2019.04.06.05
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Social Economic Levels and Anemia Events in Pregnant Women in Glugur Darat Health Center

Abstract: Background: Anemia is a condition where the hemoglobin level in the blood was lower than normal. Anemia diagnosed when the hemoglobin level was <11 gr / dl in the first and third trimesters or <10.5 gr% in the second trimester in pregnant women. WHO stated in 2010 that 40% of the causes of maternal mortality in developing countries were associated with anemia in pregnancy. Based on the Riskesdas (Basic Health Research) in 2013, the prevalence of anemia in pregnant women in Indonesia was 37.1%. One of the facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
4
4
0
Order By: Relevance
“…Another possible explanation for this finding could be that those with higher education are likely to be employed, and hence spend much of their time performing their job, leaving them with insufficient time to prepare quality food and eat adequate meals each day; instead they depend on foods sold at their workplace, which are mostly junk foods with minimal diversity. The finding of this study is similar to studies in India and Indonesia that found that anemia was more prevalent in women with secondary-level education than in women with primary-level education or who were illiterate ( 31 , 44 ). However, further studies are needed to explore the relation between the level of education, nutritional knowledge, and its adherence in pregnant women.…”
Section: Discussionsupporting
confidence: 89%
“…Another possible explanation for this finding could be that those with higher education are likely to be employed, and hence spend much of their time performing their job, leaving them with insufficient time to prepare quality food and eat adequate meals each day; instead they depend on foods sold at their workplace, which are mostly junk foods with minimal diversity. The finding of this study is similar to studies in India and Indonesia that found that anemia was more prevalent in women with secondary-level education than in women with primary-level education or who were illiterate ( 31 , 44 ). However, further studies are needed to explore the relation between the level of education, nutritional knowledge, and its adherence in pregnant women.…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, we found that lower wealth, measured using the asset index, was associated with lower umbilical cord hemoglobin levels. These findings are similar to those in other settings [ 43 ], although a study in Indonesia found no direct relationship between socioeconomic status and anemia [ 44 ]. Women with lower socioeconomic status may have limited access to nutritious food, which can lead to poor maternal nutritional status and subsequent fetal anemia [ 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to Ward et al (2009), these women have the lowest hemoglobin concentration at 30-34 weeks of pregnancy [53]. The results are consistent with others which found that the third trimester of pregnancy was associated with anemia [54], [55].…”
Section: Discussionsupporting
confidence: 77%